ZIF-8 nanoparticles as an efficient and reusable catalyst for the Knoevenagel synthesis of cyanoacrylates and 3-cyanocoumarins. Issue 52 (28th December 2016) - Kolmykov, Oleksii; Chebbat, Nassima; Commenge, Jean-Marc; Medjahdi, Ghouti; Schneider, Raphaël
Graphical abstract: Highlights: ZIF-8 mediated synthesis of cyanoacrylates and 3-cyanocoumarins is reported. The solvent plays a key role on the outcome of the reaction. 3-Cyanocoumarins are obtained under mild conditions (DMF at 80 °C). The catalyst is stable and reusable up to five cycles without any loss in activity. Abstract: Zeolitic imidazolate framework (ZIF-8) particles with an average size of ca. 355 nm and a specific surface area of 1786 m 2 .g −1 were used as an heterogenous catalyst for the Knoevenagel synthesis of α, β-unsaturated cyanoesters and 3-cyanocoumarins. The preparation of 3-cyanocoumarins was efficiently achieved using DMF as the solvent and conducting the condensation at 80 °C. When the reaction was performed in ethanol, only the intermediates α, β-unsaturated cyanoesters were obtained. The ZIF-8 catalyst can be reused up to five times without any degradation in activity. SEM and XRD analyses demonstrate the high stability of ZIF-8 crystals during the recycling test.